Upregulation of circular RNA circ_0034642 indicates unfavorable prognosis in glioma and facilitates cell proliferation and invasion via the miR‐1205/BATF3 axis. Issue 8 (2nd April 2019) - Yi, Chao; Li, Hongbin; Li, Dan; Qin, Xiangying; Wang, Jun; Liu, Yang; Liu, Zengliang; Zhang, Jiewen
Abstract: Accumulating studies demonstrate the critical role of circular RNAs (circRNAs) in the pathogenesis of various types of cancers. Previously, hsa_circ_0034642 has been found elevated in glioma tissues compared with the normal tissues, as proved by high‐throughput microarray. We further investigated its expression level in 52 paired tissues and different glioma cell lines by quantitative reverse transcription‐polymerase chain reaction. In addition, Fisher's exact test, Kaplan‐Meier curves, and Cox analyses were performed to elucidate the clinical significance of hsa_circ_0034642. For the part of functional assays, gain/loss‐of‐function assays were conducted to measure cell growth, apoptosis, and metastatic properties affected by hsa_circ_0034642. Furthermore, the mechanisms of hsa_circ_0034642 were investigated by dual‐luciferase reporter assays. As the results demonstrated, hsa_circ_0034642 was boosted in glioma tissues and cells. Overexpression of hsa_circ_0034642 was associated with clinical severity and poor prognosis. What is more, elevated hsa_circ_0034642 strikingly facilitated cell proliferation, migratory and invasive capacities, and decreased apoptotic cells. Mechanistically, hsa_circ_0034642 sponges miR‐1205. miR‐1205 regulates BATF3 level through targeting its 3′‐untranslated region. In summary, hsa_circ_0034642 might play a key role in this malignancy. Abstract : Upregulation of circular RNA circ_0034642 indicates unfavorable prognosis in patients with glioma. circ_0034642 facilitates cell proliferation and invasion via the miR‐1205/BATF3 axis.